Clinical and Prognostic Characteristics of Recurrent Intracerebral Hemorrhage: A Contrast to First-Ever ICH - Wan, Yan; Guo, Hongxiu; Bi, Rentang; Chen, Shaoli; Shen, Jing; Li, Man; Xia, Yuanpeng; Zhang, Lei; Sun, Zhou; Chen, Xiaolu; Cai, Zhuoyuan; Wang, Zhaowei; et al. (Frontiers in Aging Neuroscience, 2022)
This study aimed to compare clinical and prognostic characteristics between recurrent and first-ever ICH. 4012 patients were entered into the study, and 64% of them were male. The median age is 62 years (interquartile range, 55-71). 3750（93.5%）patients had no experience of previous ICH, and 262 (6.5%)patients were considered as recurrent ICH. We compared demographic data, baseline clinical characteristics, imaging information, hematological parameters and clinical outcomes between recurrent and first-ever ICH. We found that recurrent ICH was significantly associated with older age, more frequent history of ischemic heart disease, ischemic stroke, hypertension, and hyperlipidemia, while patients with recurrent ICH had received more previous antihypertensive therapy, and showed lower admission blood pressure (median, 160 vs 167 mmHg) and higher baseline NIHSS score (median, 10 vs 9). We also demonstrated that recurrent ICH was an independent risk factor of 3-month death and function dependence after adjusting for many potentially competitive risk factors.